COST AND REVENUE ANALYSIS OF TEMPE AMPAS BUSINESS IN IKM IN NORTH CENTRAL TIMOR REGENCY - Felisisima Afoan; Emilia Khristina Kiha (Jurnal Ekonomi, 2022)
The purpose of this study is to determine the cost of producing one-time production of tempeh pulp, as well as to determine the net income of tempeh pulp, one-time production. The method used in this study is to analyze the data by describing the data that has been collected about costs including fixed costs and non-fixed costs, receipts and net income of one-time production of tempeh pulp. Tofu dregs are waste from making tofu. Although it is waste, tofu pulp has a fairly high nutritional content, both protein and fat, so it is very possible to be processed into various types of food including tempeh pulp. The use of tofu waste, this is a new breakthrough in opening up business opportunities to start a small industry (IKM) at a low cost, because the raw material used is pulp which is very cheap and easy to obtain without knowing the season. Based on the results of the study, fixed costs are obtained by calculating all costs incurred by the Tempe Ampas Business at IKM in North Central Timor Regency, to finance all production activities that are not affected by production volumes of Rp. 232,690 one production consists of depreciation of production equipment of Rp. 7,690, - employee salaries of Rp. 150,000 and depreciation of land and buildings of Rp. 75,000. The total non-fixed cost of tempeh pulp production in the Tempe Ampas Business at IKM in North Central Timor Regency is Rp. 70,000, - consisting of raw material costs of Rp. 30,000. The total revenue from the production of tempeh pulp at the Tempe Ampas Business at IKM in North Central Timor Regency.in one production is Rp 500,000 so that the net income from the sale of tempeh tofu dregs at the Tempe Ampas Business at IKM in North Central Timor Regency. in one production Rp 197.310,- The conclusion of this study is the total production cost of one-time tempeh pulp production of the Tempe Ampas Business at IKM in North Central Timor Regency. is Rp 302,690 while the net income of tempe pulp is one time production at the Tempe Ampas Business at IKM in North Central Timor Regency. is IDR 197,310,-,-.